Regulation of let-7 and its target oncogenes (Review) - WANG, XIRUI (D.A. Spandidos, 2012)
MicroRNAs (miRNAs) are highly evolutionarily-conserved non-coding small RNAs, which were first identified in Caenorhabditis elegans. Let-7 miRNA is involved in the regulation of gene expression in cells. Several novel factors and feedback loops involved in the regulation of the synthesis of let-7 have been identified and additional let-7 target genes have been found. Let-7 has also been shown to be significantly correlated with the occurrence and development of cancer and the results of preliminary studies suggest that it is involved in the regulation of oncogenic pathways in numerous types of tumors. Let-7 is, therefore, a potential molecular target for tumor therapy. Thus, this review examined let-7 and the correlation between let-7 and oncogenic pathways in cancer.